The Relationship Between Numbers of International Tourist Arrivals and Economic Growth in The ASEAN-8: Panel Data Approach - Anggraeni, Garnis Nur (Universitas Airlangga, 2017)
In an open economy, economic growth is not only supported by international trade but may also be supported through the development of tourism. We can use international tourist arrivals as one of indicators of international tourism. This study aimed to examine the factors that influence international tourist arrivals as well as to analyze the relationship between the number of international tourist arrivals and economic growth in the Southeast Asian regions. This study uses panel data regression to 8 ASEAN countries during the period of 2000 to 2012. The results showed that the variables that identified as the determinant of international tourist arrivals are GDP per capita, secondary education enrollment gross ratio, and life expectancy. Furthermore, the number of international tourist arrivals have a significant effect on economic growth in conform with tourism-led economic growth hypothesis (TLGH). This finding infers that tourism sector could be developed as an effort to increase economic growth. Keywords: International Tourism, Economic Growth, International Tourist Arrivals, TLGH, Panel DataJEL: Z30, F43, C23